Disparities Among Cervical Cancer Patients Receiving Brachytherapy. Issue 3 (September 2019) - Bruce, Shaina F.; Joshi, Tanvi V.; Chervoneva, Inna; Yi, Misung; Chatterjee-Paer, Sudeshna; Burton, Elizabeth R.; Edelson, Mitchell I.; Sorosky, Joel I.; Shahin, Mark S.
Abstract : OBJECTIVE: To evaluate the effects of race and insurance status on the use of brachytherapy for treatment of cervical cancer. METHODS: This is a retrospective cohort study of the National Cancer Database. We identified 25, 223 patients diagnosed with stage IB2 through IVA cervical cancer who received radiation therapy during their primary treatment from 2004 to 2015. A univariate analysis was used to assess covariate association with brachytherapy. A multivariable regression model was used to evaluate the effect of race and insurance status on rates of brachytherapy treatment. The Cox proportional hazards model and the multiplicative hazard model were used to evaluate overall survival. P <.05 indicated a statistically significant difference for comparisons of primary and secondary outcomes. RESULTS: Non-Hispanic black patients received brachytherapy at a significantly lower rate than non-Hispanic white patients (odds ratio [OR] 0.93; 95% CI 0.86–0.99; P =.036); Hispanic (OR 0.93; 95% CI 0.85–1.02; P =.115) and Asian (OR 1.13; 95% CI 0.99–1.29; P =.074) patients received brachytherapy at similar rates. Compared with patients with private insurance, those who were uninsured (OR 0.72; 95% CI 0.65–0.79; P <.001), had Medicaid (OR 0.83; 95% CI 0.77–0.89; P <.001) or Medicare insurance (OR 0.85; 95% CI 0.78–0.92; P <.001) were less likely to receive brachytherapy. Brachytherapy was not found to be a mediator of race and insurance-related disparities in overall survival. CONCLUSION: Racial and insurance disparities exist for those who receive brachytherapy, with many patients not receiving the standard of care, but overall survival was not affected. Abstract : Racial and insurance disparities exist among patients who qualify for brachytherapy for treatment of their cervical cancer, yet overall survival was not affected.